1978
DOI: 10.1161/01.cir.57.3.568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cardiac glycoside in combination with propranolol on the ischemic heart of conscious dogs.

Abstract: SUMMARY The effects of coronary occlusion and of subsequent propranolol and ouabain administration were examined in 12 conscious dogs. Overall left ventricular (LV) function was assessed by measurement of LV pressure and dP/dt, and regional myocardial function was assessed by measurements of segment length (SL), velocity of SL shortening and regional myocardial "work," i.e., pressure-length loops in normal and moderately and severely ischemic zones. Regional intramyocardial electrograms were measured at the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…However, when inotropic stimulation is coupled with tachycardia, blood flow falls and contractile function deteriorates in the ischemic myocardium. These findings are also consistent with other recent studies from our laboratory on the effects of ouabain, a positive inotropic agent, which does not elicit tachycardia but exerts a salutary effect on ischemic myocardial mechanical function and blood flow when adminsitered either alone (Vatner et al, 1978b), or in combination with propranolol (Vatner et al, 1978a).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, when inotropic stimulation is coupled with tachycardia, blood flow falls and contractile function deteriorates in the ischemic myocardium. These findings are also consistent with other recent studies from our laboratory on the effects of ouabain, a positive inotropic agent, which does not elicit tachycardia but exerts a salutary effect on ischemic myocardial mechanical function and blood flow when adminsitered either alone (Vatner et al, 1978b), or in combination with propranolol (Vatner et al, 1978a).…”
Section: Discussionsupporting
confidence: 93%
“…The operation of this instrument in our laboratory has been described previously (Vatner et al, 1978a;Vatner et al, 1978b;Pagani et al, 1978;Heyndrickx et al, 1975). The instrument used in this study was modified further to provide continuous measurements of the regional electrographic potential at each crystal site.…”
Section: Methodsmentioning
confidence: 99%
“…The time at which reperfusion of ischemic tissue occurs, however, is important in determining its ability to matintaini myocardial cell integrity ancl segmeintal myocaardial functioni (11). Pagani et al (6) (24), the combination of propranolol and oubain (25), hypothermia (26), nitroglycerin (27), and nitroprusside (27). It has also been shown that greater left ventricular wall tension can be developed during reperfusioin in dogs respiring high levels of inspired oxygen during coronary occlusion than in dogs respiring room air (28).…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor is the reduction in heart rate [2], Over all there is a reduction in coronary blood flow secondary to the reduction in myocardial oxy gen consumption [3]. However, some animal experiments suggest that beta blockade may improve coronary blood flow distribution, diverting blood from the relatively well per fused myocardium into poorly perfused isch aemic parts of the heart [4],…”
mentioning
confidence: 99%